The Open Services Gateway Initiative an introductory overview. - Marples, D. (IEEE Communications magazine)
The Open Services Gateway Initiative is a consortium of more than 80 companies from around the world working together to create an infrastructure to enable the deployment of services over wide area networks to local networks and devices. In this article we outline the benefits of OSGi, typical markets, and example use cases. The article goes on to discuss the architecture of the system and the capabilities that are afforded by the latest release. The article concludes with a brief glimpse into the future specifications that are expected to result from OSGi